Narrative Impact in Church Homilies: Stories, Sayings, and Experiences - Tarigan, Thomas Natalisa; Simanjuntak, Eva Effania (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
In the modern era, homilies do not only convey religious doctrine but also address contemporary challenges in religious life. This study aims to analyse the impact of using illustrations—stories, wise sayings, and personal experiences—in homilies on the understanding and reception of God’s Word by the congregation. Descriptive qualitative research was conducted at St. Thomas the Apostle Onan Rihit Station, utilizing in-depth interviews, participatory observation, and document analysis to collect data. Findings indicate that the use of illustrations in homilies not only deepens the understanding of the Gospel teachings but also enhances the congregation's engagement with the community and the application of these teachings in daily life. Homilies are effective in enhancing resonance and attention from the congregation, demanding more empathetic and creative approaches in delivery. The results of this study underscore the importance of adaptation and innovation in homiletic practices to respond to contemporary religious life dynamics